2006
DOI: 10.1007/s00216-006-0741-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of an efficient amine-functionalized glass platform by additional silanization treatment with alkylsilane

Abstract: Aminosilane-treated molecular layers on glass surfaces are frequently used as functional platforms for biosensor preparation. All the amino groups present on the surface are not available in reactive forms, because surface amino groups interact with remaining unreacted surface silanol groups. Such nonspecific interactions might reduce the efficiency of chemical immobilization of biomolecules such as DNA, enzymes, antibodies, etc., in biosensor fabrication. To improve immobilization efficiency we have used addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 18 publications
1
39
0
1
Order By: Relevance
“…It has been also proposed that some amino group on the surface is bent toward the surface, and the bent amino group is interacted with circumjacent silanol group by hydrogen bonding or acid-base interaction to form ion pairs. Such interactions can reduce the actual reactivity of amine groups [30]. In our surface modification method forming monolayer with amino-functionalized trialkoxysilanes, however, these types of interaction of amine groups with surface silanol groups (so-called backbiting interactions) were reduced significantly and the reactivity of amino group could be maintained for a long period of time without showing any differences in the reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been also proposed that some amino group on the surface is bent toward the surface, and the bent amino group is interacted with circumjacent silanol group by hydrogen bonding or acid-base interaction to form ion pairs. Such interactions can reduce the actual reactivity of amine groups [30]. In our surface modification method forming monolayer with amino-functionalized trialkoxysilanes, however, these types of interaction of amine groups with surface silanol groups (so-called backbiting interactions) were reduced significantly and the reactivity of amino group could be maintained for a long period of time without showing any differences in the reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the binding capability of EpCAM-negative 3T3 cells was insignificant for all of the tested silanes, independent of the antibody concentration ( Figure 3). Even if both types of 'blocking silanes' (BMS, OFPOS) could prevent the bending of amino groups and facilitate proper antibody binding [14], only the APTES + OFPOS combination appeared more useful for cell recognition and binding. A remarkably higher number of attached cells was observed (Figure 4 A-I), which indicated that the antibodies immobilized on the APTES + OFPOS surface were more available for binding to cell surface antigens.…”
Section: Discussionmentioning
confidence: 99%
“…alkylsilane. Such a procedure results in the rupture of hydrogen bonds and the "straightening" of aminopropyl groups, thus increasing the access to amino groups on the modified surface [13,14]. In this study, n-butyltrimethoxysilane (BMS) and 3-(octafluoropentyloxy)-propyltriethoxysilane (OFPOS) were used as "blocking silanes" to prevent amino groups bending towards unreacted silanols ( Figure 1B, C).…”
Section: Introductionmentioning
confidence: 99%
“…Although typically constructed by immobilizing DNA on glass, silicon, or gold surfaces, there are cost and fabrication benefits to utilizing polymeric substrates [7,8]. For DNA immobilization, support substrates, for example, silicon wafer or glass, are generally coated with another chemical layer such as polymers which are included carboxyl, phosphate, aldehyde and amino groups are commonly introduced, and therefore, the relevant chemical activation steps have also been developed according to the combination of the introduced functional groups [9][10][11]. Amino groups have a great useful potential for non-covalently immobilization due to they can be positively charged by altering the pH of the buffer solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer-modified Si(1 0 0) surfaces were prepared by using PAAm (polyacrylamides) for different time periods (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) h) at room temperature. The molecular weights of polymers based on the polymerization time were examined with viscosity which can be used to determine the viscosity-average molecular weight ðM V Þ of the PAAm polymers on surface.…”
Section: Introductionmentioning
confidence: 99%